ANALISIS PEMBAGIAN MANFAAT DANA BANTUAN OPERASIONAL SEKOLAH (BOS) TAHUN 2018 DI KOTA SEMARANG - Dwi Pitari Damanik; Banatul Hayati (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2022)
BOS is a government program that aims to ease the burden on the community on education funding for quality compulsory education. This study aims to determine the distribution of benefits, the amount of average benefits and progress of the BOS subsidies among school groups based on the level of acceptance in Semarang City in 2018. This study uses Benefit Incidence Analysis (BIA) analysis techniques to see the distribution of benefits in the BOS subsidies at each level of education by combining data from the number of BOS subsidy recipients and the amount of BOS funds received at each level of education. The BIA results obtained are then interpreted in the Lorenz Curve (Lorenz Curve) to see the progress of the BOS subsidy policy. The distribution of the benefits of BOS spending for public SD, SMP and SMA is mostly enjoyed by the highest group. The distribution of benefits received by the first quintile of schools (schools with the fewest students) is less than 20% of the total BOS subsidies at each level of education.  Inequality mainly occurs at primary school levels because the Lorentz curve moves away from the equalization line. Meanwhile, the education levels for SMP and SMA are relatively more even.